Huntington's disease and steroid hormone receptors - Molikova, Radka; Bezdickova, Marcela; David, Ondrej; Bebarova, Linda (Biomedical papers, 2007)
Background: Steroid hormone receptors constitute a special group of receptors having a wide range of efficiency and distribution in the body. Androgen and estrogen receptors, and their expression in the body, are linked with attributes such as reproduction control and sexual behaviour, but their relation with behavioural models, perception, memory and stress remain unclear to date. Purpose: In this project we aim to focus on monitoring the expressive infl uence of steroid hormone receptors on embryonic tissues and subsequently, expand our study to include the expression on adult tissues such as the CNS and to monitor the developmental aspects and relations pertaining to neurodegenerative disorders, such as Huntington's disease.Material and Methods: We shall rely on immuno-histochemistry, immuno-fluorescence and RT-PCR methods for detecting steroid hormone receptors and Huntingtin-associated protein 1 in the embryonic and adult tissue.Conclusion: Mapping the expression of steroid receptors during development represents an essential step in the quest for further studies and monitoring of the expression in adult tissu
Keywords: Huntington's disease (HD)/Steroid hormone receptors (SHR)/Clinical picture